Comprehensive Assessment of Correlation of Copeptin with Some Electrolytes in Adult Patients with Chronic Kidney Disease in Babylon Governorate - Rawaa G. Abdullah; Manal F. Al-Khakani; Qasim Jawad Al-Daami (Medical Journal of Babylon)
Background: Chronic kidney disease (CKD) is a rapidly expanding public health problem typified by either an increased excretion of albumin in the urine, a reduced glomerular filtration rate, or both. Copeptin is formed by the breakdown of arginine vasopressin precursor (AVP), produced in the hypothalamus in an equimolar ratio and processed during axonal transport. AVP is an unstable peptide with a short half-life of five to twenty minutes. Compared to AVP, copeptin is a stable molecule that is simple to test. Objective: This study aims to determine whether plasma copeptin is a helpful biomarker for predicting chronic renal disease and the relationship between copeptin and certain electrolytes. Materials and Methods: This research involved a case–control study involving 88 participants, 44 individuals diagnosed with CKD, and 44 apparently healthy individuals serving as the control group. Blood samples were collected to measure copeptin, calcium, potassium, and sodium. Other variables, including age and body mass index (BMI), were also assessed. BMI was calculated by dividing weight in kilograms by height in meters squared. Statistical analyses, including Pearson correlation and receiver operating characteristic curve analysis, were conducted to evaluate the diagnostic accuracy of copeptin. Results: This study found that the copeptin concentration in the patient group increased significantly (p ˂ 0.05) compared to the control group, and the area under the curve for copeptin was 0.994. Conclusion: The results emphasize that copeptin plays a crucial role in CKD.